انتقال اثر تمارين ( بدنية - مهارية) للرشاقة الخاصة في عدد من المهارات الأساسية للاعبي كرة القدم الشباب - الخشاب، زهير قاسم حمودي; البيجواني، أدهام صالح محمود; الحيالي، معن عبدالكريم جاسم (جامعة الموصل - كلية التربية الأساسية, 2010)
The pre-skill test were executed in one day (26/5/2009) by the interchangeable style. Then, a training approach was executed of agility by using a ball with two medium circles and a swinging load movement (3:1) represented and executed in eight weeks; each course included three small training units, accordingly 24 training units were executed during the training approach. The post-skill tests were also made by the same procedures. For the sake of concluding the findings; the following statistical means were used: arithmetical mean, standard deviation, percentage, percentage of development. T- Test for the related and independent samples. The researchers concluded the following: - The occurrence of a good positive transference Exercise by (Physical- Skill) of specially Agility to all basic skills under study and the (Designing of Random Controlling Group That of Pre - and Post - Test) resulted in occurrence of significant development of these skills in comparison with the results of the pre - and post - tests and for the benefit of the post-test - the experimental group which executed the Exercise by (Physical -Skill) of specially Agility surpassed the controlling group in most of the basic skills which are (short passing, long passing, rolling and head strike). A group of recommendations were constructed, the most important of which are: 1. Concentrating on football coaches to use the Exercise by (Physical- Skill) of specially Agility in the weekly units of training, because these trainings showed good and positive impacts in improving many basic skills of football for the players of the experimental group 2. Concentrating on football coaches to use the Exercise by (Physical- Skill) of specially Agility in training the players who suffer from weaknesses in agility and low level of nerve-muscular accordance, both of which affect directly the level of skill performance of those players.
The aim of the research is to discover the : - Transference of Physical and Skill Exercise effect of special Agility in Some Basic Skills By youth footballers. - statistical significanc at differences between the pre - and post - tests for the two groups; the control and experimental group on some basic skills by youth footballers. - the percentage of development on some football basic skills between the two groups: the experimental and control groups. The descriptive approach was used for its appropriateness to the nature of the study. The collection of the society of the chosen study was randomly which consisted of youth players of Nineveh Club for the season 2008-2009, and they were 28 players. As for the sample of the study; it consisted of 20 players divided into two groups; one of them is the experimental group and the other is the control group, with 10 players for each group. So. the percentage was %71.34 out of the total collection of the study. Homogeneity was achieved between the two groups under study in the variables of age. weight and height. Equality was also achieved between the two groups under study in the variables of skills (rolling, short passing, long passing, short range targeting and head striking), which the persons who are responsible for the experiment agreed about. The experimental design was used and called (Designing of Random Controlling Group That of Pre - and Post - Test). As for the steps of the study; the first step was codifying a number of (physical -skill) trainings concerning agility by using the ball and without it, while the second was making personal interviews with some specialists to identify’ the most appropriate trainings to the sample of the study. The training approach was made and demonstrated to these specialists in order to make the required revisions of it. Also, three pilot experiments were made to know the capability of executing the skill tests and eliminate the difficulties that they might face, and to make sure of rest times among repetitions and groups. As for the third experiment; it aimed at the possibility of executing a full training unit for the sample of the study.
تم أجراء الاختبارات المهارية القبلية في يوم واحد بتاريخ (26/5/2009) وبأسلوب العمل المتبادل ، وبعدها نفذ المنهاج التدريبي لتدريبات الرشاقة الخاصة لدورتين متوسطتين وبتموج حركة حمل (3: 1) وبواقع ثماني دورات أسبوعية إذ تضمنت كل دورة صغيرة ثلاث وحدات تدريبية وعليه تم تنفيذ (24) وحدة تدريبية خلال المنهاج التدريبي ، وتم أجراء الاختبارات المهارية البعدية بنفس الإجراءات التي تم اعتمادها في تنفيذ الاختبارات القبلية ولاستخلاص النتائج تم استخدام المعالجات الإحصائية الآتيه: (الوسط الحسابي ، الانحراف المعياري ، النسبة المئوية ، نسبة التطور ، اختبار (ت) للعينات المرتبطة والمستقلة). وتوصل الباحثون إلى عدد من الاستنتاجات أهمها: - حدوث انتقال إيجابي جيد من (التمارين البدنية – المهارية)، للرشاقة الخاصة إلى جميع المهارات الأساسية قيد البحث وهي (التمريرة القصيرة ، التمريرة الطويلة ، التهديف القريب، الدحرجة ، وضرب الكرة بالرأس) والذي أدى إلى حصول تطوراً معنوياً لهذه المهارات عند مقارنة نتائج الاختبارات القبلية والبعدية ولصالح الاختبار البعدي. - تفوقت المجموعة التجريبية التي نفذت (التمارين البدنية – المهارية)، للرشاقة الخاصة على المجموعة الضابطة في معظم المهارات الأساسية وهي (التمريرة القصيرة ، التمريرة الطويلة، الدحرجة ، وضرب الكرة بالرأس) عند مقارنة نتائج الاختبارات البعدية بين المجموعتين التجريبية والضابطة. وتم وضع مجموعة من التوصيات أهمها: - التأكيد على مدربي كرة القدم باستخدام التمارين (البدنية – المهارية)، للرشاقة الخاصة في الوحدات التدريبية الأسبوعية، وذلك لما أظهرته هذه التدريبات من تأثيرات إيجابية جيدة في تحسين العديد من المهارات الأساسية في كرة القدم للاعبي المجموعة التجريبية. - يمكن للمدربين الاعتماد على التمارين (البدنية – المهارية)، للرشاقة الخاصة باستخدام الكرة، وبدون استخدام الكرة في تنمية نظام الطاقة الفوسفاجيني من خلال زيادة كفاءة عمل النظام لإنتاج الطاقة الآنية التي يحتاجها اللاعبون في أداء كافة المهارات الأساسية بكرة القدم .
هدف البحث الكشف عما يأتي: - انتقال اثر تمارين (بدنية – مهارية)، للرشاقة الخاصة في عدد من المهارات الأساسية للاعبي كرة القدم الشباب. - دلالة الفروق الإحصائية بين الاختبارين البعديين للمجموعتين التجريبية والضابطة في عدد من المهارات الأساسية للاعبي كرة القدم الشباب. - نسبة التطور في عدد من المهارات الأساسية بكرة القدم بين المجموعتين التجريبية والضابطة. وتم استخدام المنهج التجريبي لملاءمته وطبيعة مشكلة البحث ، وحددت عينة البحث بالطريقة العمدية والمؤلفة من لاعبي شباب نادي نينوى بكرة القدم للموسم الكروي (2008/ 2009) والبالغ عددهم (28) لاعباً ، أما عينة البحث الرئيسية فتكونت من (20) لاعباً ، قسموا إلى مجموعتين إحداهما تجريبية والأخرى ضابطة وبواقع (10)، لاعبين في كل مجموعة، وبذلك بلغت النسبة المئوية لعينة البحث (71.43%) من عينة البحث الكلية ، وتم تحقيق التكافؤ بين مجموعتي البحث في متغيرات (العمر، والوزن ، والطول) وفي المتغيرات المهارية قيد البحث وهي (الدحرجة، والتمريرة القصيرة ، والتمريرة الطويلة، والتهديف القريب) التي تم الاتفاق عليها من قبل السادة المتخصصين، وأستخدم التصميم التجريبي الذي أطلق عليه اسم "تصميم المجموعات الضابطة العشوائية الاختيار ذات الاختبار القبلي والبعدي". أما خطوات البحث الرئيسية فقد كانت الخطوة الأولى عملية تقنين عدداً من التمارين (البدنية – المهارية)، لصفة الرشاقة الخاصة مع الكرة وبدون كرة، في حين كانت الخطوة الثانية إجراء المقابلة الشخصية مع بعض السادة المختصين لتحديد أفضل التمارين الملائمة لعينة البحث، وبعدها تم وضع المنهاج التدريبي وعرض على بعض السادة المختصين لأجراء التعديلات اللازمة عليه ، كما أجريت ثلاثة تجارب استطلاعية فكانت التجربة الأولى لمعرفة إمكانية تنفيذ الاختبارات المهارية وتلافي الصعوبات التي تواجههم ، أما التجربة الثانية فقد هدفت إلى التعرف على إمكانية إجراء التمارين المختارة والتأكد من أزمنة الراحة بين التكرارات والمجاميع ، في حين هدفت التجربة الثالثة معرفة إمكانية تنفيذ وحدة تدريبية كاملة لعينة البحث التجريبية.
Keywords: الأداء المهاري; التدريب الرياضي; كرة القدم